ANALISIS PENGARUH DEBT TO EQUITY RATIO (DER) DAN NET PROFIT MARGIN (NPM) TERHADAP RETURN SAHAM PADA PT. HANJAYA MANDALA SAMPOERNA, TBK - Indah Damayanti; Nafisah Nurulrahmatia (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
This research aims to determine the influence of Debt to equity ratio and Net profit margin partially or simultaneously on stock returns at PT. HM Sampoerna Tbk for 15 years, namely from 2008-2022. This research variable consists of Debt to equity ratio (X1), Net profit margin (X2), and stock returns (Y). The data collection method uses the documentation method. The data analysis method uses multiple linear regression analysis. The results of the F test show that simultaneously the independent variables DER and NPM have a positive and significant effect on stock returns. The results of the t test show that partially: 1) Debt to equity ratio (DER) does not have a partially significant effect on partial stock returns at PT. HM Sampoerna Tbk. 2) Net profit margin (NPM) does not have a partially significant effect on partial stock returns at PT. HM Sampoerna Tbk.